2017
DOI: 10.3892/etm.2017.5582
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of inflammatory bowel disease risk factors in 4 families in central China

Abstract: The prevalence of inflammatory bowel disease (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), is increasing markedly in China. The present study performed pedigree analysis of 4 families with a history of IBD and investigated the association of genetic and environmental factors with susceptibility to IBD. A total of 10 IBD patients (8 CD patients and 2 UC patients) and 90 family members were included in the present study. The clinical characteristics of familial subjects were compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…However, these studies found that the common variants in NOD2/CARD15 found in Caucasians with CD are not associated with CD in the both Chinese Zhuang and Han population. Further analysis also revealed that CARD15 gene polymorphism was not associated UC in Chinese populations ( 38 , 39 ). Studies comparing IBD-related susceptibility genes between Chinese patients and Western patients might answer this question in the future.…”
Section: Resultsmentioning
confidence: 92%
“…However, these studies found that the common variants in NOD2/CARD15 found in Caucasians with CD are not associated with CD in the both Chinese Zhuang and Han population. Further analysis also revealed that CARD15 gene polymorphism was not associated UC in Chinese populations ( 38 , 39 ). Studies comparing IBD-related susceptibility genes between Chinese patients and Western patients might answer this question in the future.…”
Section: Resultsmentioning
confidence: 92%
“…A Chinese study reported family history describing the most commonly affected types of relatives were cousin (41.1%), sibling (37.5%), and parent (28.6%). 16 The explanation for different family history of IBD among different countries is possibly that families have different genetic backgrounds, and often different environments and lifestyles. Interestingly, maternal family history of IBD was found not significantly associated with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…If the recipient’s lifestyle does not change to that of the donor after FMT, then the effect on the recipient’s microbial makeup may disappear over time. People living in different continents and regions have their own unique dietary habits[ 106 ]. The diet of Europeans is rich in cheese, butter and other high-fat and high-calorie foods, while the diet of Africans is low in calories and high in dietary fiber[ 107 ].…”
Section: Concomitant Lifestyle and Dietmentioning
confidence: 99%